Facebook Birthday Postings from a Language Ecology Perspective in Russian, German, American English, and French - Olga Karamalak (Journal of Language and Education, 2016)
The aim of the paper is to examine Facebook postings from an ecological language perspective as a special type of discourse of “everyday life” with an orientating function, to evaluate the environmental potential of this network that influences the character of the posts, and to determine cultural differences in thinking and expressing birthday greetings on the Facebook platform.The paper outlines some specific features of the Facebook environment or niche such as the reduced characters of the message, the use of abbreviations, simple structures, merging and interaction of written and spoken languages, and the use of graphical signs to convey emotions. The methodological approach was to compile a database by randomly gathering, from various Facebook timelines, 680 birthday postings in Russian, American English, German, and French. The posts were then analyzed according to three dimensions: (1) focus of the greetings on the specific day or years to come / life in general (Western vs. non-Western countries, analytical vs. holistic mindsets); (2) use of nominal structures; (3) stress/emphasis on characteristic features of a person, compliments.Various psycholinguistic and cultural aspects of the verbal greetings from the timelines of Russian, American, German, and French users of the social net are singled out in terms of holistic and analytical types of critical thinking. The data collection shows that while Russians and Germans predominantly display holistic thinking, as expressed in birthday postings of a general character and wishes in general for the upcoming year or years to come, Americans and the French display analytical thinking as their birthday posts are more focused on that special day. Most birthday postings are usually short and have one similar pattern. Americans use a lot of praise and stress personal relations. French postings are very emotional often expressing love and kisses. This study shows that analysis of Facebook birthday postings should be multimodal and complex, taking into account a complex interaction of a number of internal and external factors and a personal inclusion into socio-cultural interactions.